2021
DOI: 10.1021/acs.jpclett.0c03774
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Reversible Dual Fluorescent Switches for Multimodality Optical Memory

Abstract: Fluorescent photoswitches are highly attractive, because they hold great promises for photonic devices and imaging. However, a limited number of reversible switches with a response to light have been achieved in the solid state. Here, we report reversible dual fluorescent photoswitching characteristics in the solid state of spiropyran (SP)−functionalized tetraphenylethene (TPE) derivatives. These photoswitches exhibit two distinct and selectively addressable states, a cyan fluorescence and a red fluorescence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…Similarly, Yang and coworkers presented two unique examples of photoresponsive materials (TPEA‐SP and TPEB‐SP) with reversible dual fluorescence switches in solid states. [ 88 ] SP can perform reversible photoisomerization between the closed state and the MC open form under the stimuli of UV and visible irradiation. The experimental and theoretical calculation results show that under UV light, the intramolecular energy transfer from TPE to MC moiety can take place, which leads to the transformation of the fluorescence between bright cyan and red.…”
Section: Manipulating Aggregation Structurementioning
confidence: 99%
“…Similarly, Yang and coworkers presented two unique examples of photoresponsive materials (TPEA‐SP and TPEB‐SP) with reversible dual fluorescence switches in solid states. [ 88 ] SP can perform reversible photoisomerization between the closed state and the MC open form under the stimuli of UV and visible irradiation. The experimental and theoretical calculation results show that under UV light, the intramolecular energy transfer from TPE to MC moiety can take place, which leads to the transformation of the fluorescence between bright cyan and red.…”
Section: Manipulating Aggregation Structurementioning
confidence: 99%
“…It is noteworthy that the single molecules of BOSA‐SP and BOSA‐MC occupied volumes of 66.35±0.003 and 65.30±0.002, respectively. Compared with the reported high volume of the SP (69.00±0.21) and MC (67.60±0.26) moieties, [2c] there was a significant reduction in the volume occupied by SP and its photoisomers (MC) after the twisted BOSA moiety was connected, which suggests that this connection created a large intermolecular space; the twisted BOSA moiety increased the intermolecular distance of the MC and SP moieties in the solid state, which enabled the “trigger” light to induce reversible reversion between MC and SP in the solid state.…”
Section: Resultsmentioning
confidence: 71%
“…Detailed time‐dependent spectroscopy studies showed that under continuous UV‐light irradiation, the intensity of the new absorption (576 nm) and emission peaks (692 nm) gradually intensified, and the emission peak centered at 532 nm gradually declined (Figures 1c and d). These results indicate that UV light successfully triggered the switch from BOSA‐SP to BOSA‐MC in the solid state (Figure 1a) [2b,c] . And the absorbance of BOSA‐MC solid film dropped less after 48 hours of non‐stop testing in a dark environment (Figure S2).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations